Pola Interaksi Sosial antar Pedagang Oleh - Oleh di Kawasan Wisata Bahari Lamongan - Muhammad Nouvan Zahid (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
The lives of souvenir traders reveal diverse patterns of social interaction that do not always align with expectations or ideal norms, as they involve two opposing forms of interaction: associative (positive) and dissociative (negative) social interaction. Although positive interactions exist, negative interactions also emerge in practice, making the reality of daily life among souvenir traders more diverse. Based on these conditions, the research question in this study is: why do the social interaction patterns among souvenir traders take the form of associative and dissociative interactions? This study applies Gillin and Gillin’s social interaction theory as the theoretical framework to examine the forms and processes of interaction that emerge, whether they are associative or dissociative. The method used is qualitative research, while data analysis is conducted using the Miles and Huberman model. The research findings show that associative social interaction manifests through cooperation, accommodation, and assimilation, which arise from the need to maintain social relationships and ensure the smooth operation of souvenir trade activities for example, by helping one another, adapting, and following local customs. On the other hand, dissociative social interactions manifest as competition, conflict, and tension rooted in economic interests and situations that can create friction. These two primary forms do not operate in isolation but coexist within the trading environment. The interdependence and proximity of activities foster mutually supportive relationships, yet shared economic goals also give rise to competition, differences, and tension. Thus, social interactions among souvenir traders emerge from a balance between efforts to maintain social relationships and efforts to pursue self-interest.
Finalisasi 1 Juli 2026_Yudi
Keywords: Social interaction; Souvenir traders